Penerapan Model Pembelajaran Student Facilitator and Explaining dalam Meningkatkan Hasil Belajar Siswa pada M.P IPS Terpadu di UPTD SMP Negeri 8 Gunungsitoli - Telaumbanua, Siska Novinta; Laoli, Bezisokhi; Lahagu, Arianto; Laoli, Eka Septianti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this study was to evaluate the effectiveness of applying the Student Facilitator and Explaining (SFAE) learning model in improving student learning outcomes at UPTD SMP Negeri 8 Gunungsitoli. This research was conducted at UPTD SMP Negeri 8 Gunungsitoli during the 2023/2024 academic year. The research method used was Classroom Action Research (PTK) which was carried out in two cycles, each with a structured evaluation of teacher ability, student activeness, and student learning outcomes. The results showed that in the first cycle, the teacher's ability to apply the SFAE model reached an average of 49.21%, increasing significantly to 85.93% in the second cycle. Student activeness also increased from an average of 62% to 84.94% between the first and second cycles. Student learning outcomes showed a significant increase from an average of 74.40% to 83.59%, with the percentage of learning completeness increasing from 48.14% to 88.88%. The conclusion of this study is that the application of the SFAE model significantly improved student engagement and learning outcomes at UPTD SMP Negeri 8 Gunungsitoli, indicating that this model is effective in improving learning quality. This research supports the use of interactive and visual methods in the learning process to achieve better educational outcomes.